Comparative Evaluation Of Diabetogenic Potentials Of Alloxan, Streptozotocin And Their Cocktail In Rabbits (Oryctolagus Cuniculas) (Applied Biological Research, 2016)
Comparative diabetogenic potentials of alloxan, streptozotocin (STZ) and alloxan-streptozotocin cocktail in rabbits was investigated. ‘New  Zealand White’ rabbits, 1-1.5 kg body weight (b.w.), were administered100 mg alloxan kg-1 b.w and 65 mg STZ kg-1 b.w, individually and 50 mg  alloxan kg-1 b.w. and 35 mg STZ kg-1 b.w. cocktail, as single intravenous  dose. Fasting blood glucose levels were monitored on day 0, 3, 5, and 7.  Rabbits with fasting blood glucose levels > 200 mg dL-1 were considered  diabetic. Alloxan caused early induction of sustained hyperglycaemia  while relatively resistant rabbits revealed mild hyperglycaemia on day 3  followed by progressive recovery. In contrast, alloxan-STZ cocktail  caused a progressive increase in hyperglycaemic animals upto 7 days.  However, the overall diabetogenic efficiency was less than alloxan alone.  The hyperglycaemia was mild to moderate when alloxan-STZ cocktail  was used as compared to that induced by alloxan alone which resulted in  moderate to severe hyperglycaemia. STZ failed to induce significant and  sustained hyperglycaemia in rabbits. It may be concluded that low dose  alloxan-STZ cocktail is a choice for the induction of diabetic rabbit  model whereas rabbits appeared relatively resistant to diabetogenic  effects of STZ. Further, spontaneous progressive recovery warrant extra  caution in evolving and extrapolating results while using such models.
Keywords: Alloxan; cocktail; diabetes mellitus; rabbits; streptozotocin